2019
DOI: 10.1007/s41105-019-00207-2
|View full text |Cite
|
Sign up to set email alerts
|

Factors determining sleep in patients hospitalised in ICUs in a hospital in Northern Poland

Abstract: Evaluation of sleep quality and sleep-disturbing factors in patients in an Intensive Care Unit (ICU). Over 8 months, 83 persons were examined as part of the recruitment of patients hospitalised in the ICU. The interviewer conducted interviews with the patients on the third day following their discharge from the ICU. Patients had to successfully complete the Short Portable Mental Status Questionnaire. The patients whose results reflected their normal mental status were administered the Richards-Campbell Sleep Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
(34 reference statements)
0
7
0
Order By: Relevance
“…More than 50% of critically ill patients have shown sleep disturbances [ 6 ]. Various environmental [ 7 , 8 ] and nonenvironmental factors [ 4 , 7 ] effect sleep in the ICU. Major environmental factors reported by Lewandowska et al were the measurement of vital signs, light, blood collection, diagnostic tests, and noise, respectively [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More than 50% of critically ill patients have shown sleep disturbances [ 6 ]. Various environmental [ 7 , 8 ] and nonenvironmental factors [ 4 , 7 ] effect sleep in the ICU. Major environmental factors reported by Lewandowska et al were the measurement of vital signs, light, blood collection, diagnostic tests, and noise, respectively [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Various environmental [ 7 , 8 ] and nonenvironmental factors [ 4 , 7 ] effect sleep in the ICU. Major environmental factors reported by Lewandowska et al were the measurement of vital signs, light, blood collection, diagnostic tests, and noise, respectively [ 8 ]. Likewise, Lori J Delaney et al reported noise, light, and clinical care interactions [ 9 ], whereas Ding et al reported that psychological factors outweigh the environmental factors in contributing to poor sleep [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacological sedation is becoming frequently used in various clinical situations such as invasive endoscopy, minor surgery, radiological examinations for children, and mechanical ventilation in ICU [10,25,26,27]. Apneas and hypopneas during sedation were spontaneously terminated either with or without cortical arousal in our patients.…”
Section: Discussionmentioning
confidence: 82%
“…It is therefore evident that medical awareness of the impact of sleep disorders on hospitalized patients is of vital importance, and that knowledge of the major factors that disturb sleep during hospitalization will allow both researchers and hospital staff to systematically evaluate and treat sleep issues. Although inadequate sleep has a demonstrated negative association with health care outcomes, to date, few studies have examined sleep in intensive rehabilitation units or its association with functional independence outcomes [13][14][15].…”
Section: Introductionmentioning
confidence: 99%